2019
DOI: 10.2478/hukin-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Whey Protein Hydrolysate and Milk-Based Formulated Drinks on Recovery of Strength and Power Following Acute Resistance Exercise

Abstract: Intensive resistance exercise can result in exercise-induced-muscle-damage, which commonly leads to reductions in acute muscle function. Post-exercise ingestion of carbohydrate-protein mixtures intends to attenuate these effects. This study aimed to compare the effectiveness of whey protein hydrolysate and milk-based formulated drinks on recovery of muscle function following resistance exercise. Thirty resistance-trained males were randomly assigned to either whey hydrolysate and dextrose drink (WH), milk-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
2
4
0
1
Order By: Relevance
“…Specifically, concentric and eccentric isokinetic peak torque decreased at 24 h after speed-endurance training 1 similarly in all trials, as previously reported [ 6 ], without any effect of protein supplementation. In line with our observations, previous research revealed that WP hydrolysate and milk-based supplementation had no impact on isokinetic strength performance recovery following resistance exercise [ 31 ]. However, one study revealed that WP isolate (1.5 g/kg/day) attenuated the decline of isometric and isokinetic performance following exercise-induced muscle damage [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, concentric and eccentric isokinetic peak torque decreased at 24 h after speed-endurance training 1 similarly in all trials, as previously reported [ 6 ], without any effect of protein supplementation. In line with our observations, previous research revealed that WP hydrolysate and milk-based supplementation had no impact on isokinetic strength performance recovery following resistance exercise [ 31 ]. However, one study revealed that WP isolate (1.5 g/kg/day) attenuated the decline of isometric and isokinetic performance following exercise-induced muscle damage [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings demonstrated that the supplementation with whey hydrolysate led to lower CK levels at 48h and attenuated the decline in muscle function (evidenced by an improved reactive strength index and higher flexibility). These positive short-term effects of hydrolysates are in accordance with the findings from further studies [43,73], although some researchers reported contradictory results [74].…”
Section: Effects On Muscle Damagesupporting
confidence: 89%
“…These authors found no significant interactions between EIMD markers and milk protein timing (pre, post, or 24 h post-exercise), dosage (17 or 34 g), or type (milk or flavoured milk plus carbohydrate) [ 36 , 38 , 39 ]. Similarly, ingesting flavoured milk relative to an isonitrogenous dose of whey protein hydrolysate did not impact muscle damage following whole-body resistance exercise in trained males [ 70 ]. Conversely, Buckley et al [ 44 ] indicate that the type of ingested protein influences EIMD.…”
Section: Discussionmentioning
confidence: 99%